Resolving Low Cloud Feedbacks Globally With E3SM High‐Res MMF: Agreement With LES but Stronger Shortwave Effects - Liran Peng; Peter N. Blossey; Walter M. Hannah; Christopher S. Bretherton; Christopher R. Terai; Andrea M. Jenney; Savannah L. Ferretti; Hossein Parishani; Michael S. Pritchard (Journal of Advances in Modeling Earth Systems)
Abstract This study investigates low cloud feedback in a warmer climate using global simulations from the High‐Resolution Multi‐scale Modeling Framework (HR‐MMF), which explicitly simulates small‐scale eddies globally. Two 5‐year simulations—one with present‐day sea surface temperatures (SSTs) and a second with SSTs warmed uniformly by 4 K—reveal a positive global shortwave cloud radiative effect (SWCRE = 0.3 W/m2/K), comparable to estimates from CMIP models. As the climate warms, significant reductions in low cloud cover occur over stratocumulus regions. This study is the first attempt to compare HR‐MMF results with predictions from idealized large‐eddy simulations from the CGILS intercomparison. Despite different underlying assumptions, we find qualitative agreement in SWCRE and inversion height changes between HR‐MMF and CGILS predictions. This suggests reasonable credibility for the CGILS framework in predicting cloud responses under the out‐of‐sample conditions found in HR‐MMF. However, the HR‐MMF exhibits stronger SWCRE changes than predicted by CGILS. We explore potential causes for this discrepancy, examining variations in cloud‐controlling factors (CCFs) and cloud conditions. Our results show a fairly homogeneous SWCRE response, with little systematic variation tied to the variations in CCFs. This reveals a dominant role for SST forcing in modulating SWCRE.